2017
DOI: 10.1093/nar/gkx087
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide identification of physically clustered genes suggests chromatin-level co-regulation in male reproductive development in Arabidopsis thaliana

Abstract: Co-expression of physically linked genes occurs surprisingly frequently in eukaryotes. Such chromosomal clustering may confer a selective advantage as it enables coordinated gene regulation at the chromatin level. We studied the chromosomal organization of genes involved in male reproductive development in Arabidopsis thaliana. We developed an in-silico tool to identify physical clusters of co-regulated genes from gene expression data. We identified 17 clusters (96 genes) involved in stamen development and act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
32
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(33 citation statements)
references
References 54 publications
1
32
0
Order By: Relevance
“…In ms1 mutants, abnormal exine bacula are observed, with a lack of vesicles associated with intine formation, suggesting that MS1 is involved in pollen wall and coat formation ( Wilson et al , 2001 ; Ito and Shinozaki, 2002 ; Vizcay-Barrena and Wilson, 2006 ; Ito et al , 2007 ). Reimegård et al (2017) found 17 physically converged gene clusters acting downstream of MS1; Clusters #7 and #15 contain the pollen coat extracellular lipase (EXL4–EXL6) proteins and the GRP–oleosin chimeric proteins, respectively ( Fig. 1a , b ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In ms1 mutants, abnormal exine bacula are observed, with a lack of vesicles associated with intine formation, suggesting that MS1 is involved in pollen wall and coat formation ( Wilson et al , 2001 ; Ito and Shinozaki, 2002 ; Vizcay-Barrena and Wilson, 2006 ; Ito et al , 2007 ). Reimegård et al (2017) found 17 physically converged gene clusters acting downstream of MS1; Clusters #7 and #15 contain the pollen coat extracellular lipase (EXL4–EXL6) proteins and the GRP–oleosin chimeric proteins, respectively ( Fig. 1a , b ).…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, these physically clustered and co-regulated genes include not only tandem duplicated genes, but also non-homologous genes. For instance, the ANTHER27/BETA GLUCOSIDASE 20 ( ATA27/BGLU20 ), which locates to Cluster #7, has no homology with any of the adjacent lipases, but shows co-expression with EXL4–EXL6 ( Reimegård et al , 2017 ). ATA27/BGLU20 has tapetum-specific expression and has been proposed as playing an indispensable role in pollen development ( Rubinelli et al , 1998 ; Dong et al , 2019 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Earlier studies of gene expression in several plant species have pointed out that it is common to observe co-expression between neighboring genes [52][53][54][55]. An explanation of this phenomenon is that neighboring genes (especially those with overlapping divergent promoters) share some common cis-regulatory elements.…”
Section: Co-expression Of Genesmentioning
confidence: 99%
“…Despite this trend, certain groups of genes remain close in the genome over long evolutionary distances, which suggests that selection acts to maintain their genomic colocalization. Genes within such conserved clusters may have functional links (Lee and Sonnhammer, 2003;Wisecaver et al, 2014), and can be transcribed in a coordinated manner (Boutanaev et al, 2002;Reimegård et al, 2017). Comparative genomics can be used to uncover groups of genes that remain significantly closer than expected, despite extensive gene order shuffling.…”
Section: Introductionmentioning
confidence: 99%